The subcutaneous route to insulin dependent diabetes therapy. - Bellazzi, R. (IEEE Engineering in medicine and biology magazine)
Discusses closed-loop and partially closed-loop control strategies for insulin delivery and measuring glucose concentration. The authors review the subcutaneous closed- and partially closed-loop strategies that have been proposed and tested in recent years for insulin-dependent diabetes therapy. Focus is on control, modeling, and information technology aspects, and future directions of research are also outlined. This survey complements earlier reviews concerning control approaches and application of computers in diabetes care